ESSENCE OF SOCIAL INSURANCE, ITS ROLE AND PLACE IN THE SYSTEM OF SOCIAL PROTECTION OF THE POPULATION - Akhmejanova G. B.; Mussabekova N. M.; Voronova T. E.; Batay A.; Grigorieva R. V. (Scientific Journal of Pedagogy and Economics, 2021)
This article discusses the formation of the social protection system in the Republic of Kazakhstan and its component such as social insurance, the place and role of the Head of State - the Leader of the Nation in the implementation of these reforms in Kazakhstan. The essence, goals, principles of social insurance were determined in this article. The points of view of the scientists and experts were studied. The interpretation of the social insurance, comparative analysis of the concepts of social security, social assistance, benefits and compensation was researched. The state could not stay out of this complex process and began to actively participate in it. Moreover, this participation has been carried out in two directions. The first is the creation of the state insurance system, which either protects the states’, mainly property interests, or protects certain socially vulnerable groups of the population. The second is the creation of the mechanism for legal regulation of insurance relations as the special group of the public relations. In the legislation of any country extensive block called legislation on insurance. In the market economy, based on the private property, the main driver of insurance is the desire of the owner to protect his property. At the same time, the growth of welfare causes the individual to take care of himself, which expands the scope of personal insurance.